Protective effect of anakinra on audiovestibular function in a murine model of endolymphatic hydrops - Zhang, Na; Li, Na; Wang, Siyue; Xu, Wandi; Liu, Jiahui; Lyu, Yafeng; Li, Xiaofei; Song, Yongdong; Kong, Ligang; Liu, Yalan; Guo, Jia; Fan, Zhaomin; et al. (Frontiers in Cellular Neuroscience, 2022)
Meniere’s disease (MD), a common disease in the inner ear, is characterized by an increase in endolymph in the cochlear duct and vestibular labyrinth. The pathophysiology of the condition appears to be the immune response. Studies have shown that basal levels of the IL-1β increased in some MD patients. Here, we used a murine model of endolymphatic hydrops (EH) to study the effect of anakinra on auditory and vestibular function. Mice were intraperitoneal injected with anakinra or saline before LPS by postauricular injection. Weight and disease severity were measured, histologic changes in auditory were assessed, and inflammation state was evaluated. We found that anakinra therapy reduced LPS-induced EH, alleviated LPS-induced hearing loss and vestibular dysfunction, and inhibited the expression of the inflammatory cytokines and macrophage infiltration in the cochlea of mice. We further demonstrated that anakinra ameliorated the disorganization and degeneration of myelin sheath, and reduced the neuron damage in cochlea of EH mice. Consequently, anakinra contributes to a promising therapeutic approach to MD, by restricting EH, alleviating auditory and vestibular function, inhibiting inflammation of the inner ear and protecting the cochlear nerve. Further investigations are needed to assess the potential therapeutic benefits of anakinra in patients with MD.